Neuroimaging and neurological outcome of children with acute encephalitis - Pöyhönen Heidi M.; Nyman Mikko J.; Peltola Ville T.; Löyttyniemi Eliisa S.; Lähdesmäki Tuire T. (WILEY, 2022)
Aim: To investigate the severity of acute phase magnetic resonance imaging (MRI) findings and severity of acute illness as risk factors for disability after recovery from encephalitis.
Method: Children  with  encephalitis  (n  =  98;  median  age  6  years  10  months,  inter-quartile  range  3  years–11  years  6  months;  59  males,  39  females)  treated  in  Turku  University Hospital during the years 1995 to 2016 were identified in this retrospec-tive cohort study. The acute phase (<2 months of symptom onset) brain MRIs were re-evaluated and classified based on the severity of neuroimaging finding by a neu-roradiologist.  Neurological  outcome  at  discharge,  at  short-term  (<3  months  from  discharge)  follow-up,  and  at  long-term  (>1  year  from  discharge)  follow-up  was  as-sessed from medical records using the Glasgow Outcome Scale.
Results: Long-term recovery was poor in 24 of 82 (29%) children with follow-up data. Two children died, eight had severe disability, and 14 had moderate disability. Acute phase MRI was available for re-evaluation from 74 of 82 patients with follow-up data. The increasing severity of MRI findings was associated with need for ventilator ther-apy and with poor recovery.
Interpretation: The risk for poor recovery in paediatric encephalitis is high, and it is associated with the severity of MRI findings.